Impact of Obesity on Pediatric Acute Recurrent and Chronic Pancreatitis. Issue 8 (September 2018) - Uc, Aliye; Zimmerman, M. Bridget; Wilschanski, Michael; Werlin, Steven L.; Troendle, David; Shah, Uzma; Schwarzenberg, Sarah Jane; Rhee, Sue; Pohl, John F.; Perito, Emily R.; Palermo, Joseph J.; Ooi, Chee Y.; et al.
Abstract : Objective: The aim of this study was to assess the impact of obesity on pediatric acute recurrent pancreatitis or chronic pancreatitis (CP). Methods: We determined body mass index (BMI) status at enrollment in INSPPIRE (IN ternationalS tudy group ofP ediatricP ancreatitis:I n search for a cuRE ) cohort using CDC criteria for pediatric-specific BMI percentiles. We used the Cochran-Armitage test to assess trends and the Jonckheere-Terpstra test to determine associations. Results: Of 446 subjects (acute recurrent pancreatitis, n = 241; CP, n = 205), 22 were underweight, 258 normal weight, 75 overweight, and 91 were obese. The BMI groups were similar in sex, race, and age at presentation. Hypertriglyceridemia was more common in overweight or obese. Obese children were less likely to have CP and more likely to have acute inflammation on imaging. Compared with children with normal weight, obese or overweight children were older at first acute pancreatitis episode and diagnosed with CP at an older age. Obese or overweight children were less likely to undergo medical or endoscopic treatment, develop exocrine pancreatic insufficiency, and require total pancreatectomy with islet autotransplantation. Diabetes was similar among all groups. Conclusions: Obesity or overweight seems to delay the initial acute pancreatitis episode and diagnosis of CP compared with normal weight or underweight. The impact of obesity on pediatric CP progression and severity deserves further study. Abstract : Supplemental digital content is available in the text.